2022
DOI: 10.1021/acs.inorgchem.2c01328
|View full text |Cite
|
Sign up to set email alerts
|

C–H Bond Activation and C–C Coupling of Methane on a Single Cationic Platinum Center: A Spectroscopic and Theoretical Study

Abstract: We spectroscopically investigated the activation products resulting from reacting one and multiple methane molecules with Pt + ions. Pt + ions were formed by laser ablation of a metal target and were cooled to the electronic ground state in a supersonic expansion. The ions were then transferred to a room temperature ion trap, where they were reacted with methane at various partial pressures in an argon buffer gas. Product masses observed were [Pt,C,2H] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Note that the single dehydrogenation observed is in contrast to the observations of Irikura and Beauchamp, but this difference could be attributed to the high-pressure conditions of the molecular beam versus the low-pressure conditions in the ICR experiments. This conclusion was confirmed by later repeating the experiment using a different apparatus operating under low-pressure conditions . Now, both PtC 2 H 4 + and PtC 4 H 8 + (but no PtC 3 H 6 + ) were observed and shown to have Pt + (ethene) and Pt + (ethene) 2 structures.…”
Section: Are There Other Adiabaticities/diabaticities Besides Spin?mentioning
confidence: 56%
See 1 more Smart Citation
“…Note that the single dehydrogenation observed is in contrast to the observations of Irikura and Beauchamp, but this difference could be attributed to the high-pressure conditions of the molecular beam versus the low-pressure conditions in the ICR experiments. This conclusion was confirmed by later repeating the experiment using a different apparatus operating under low-pressure conditions . Now, both PtC 2 H 4 + and PtC 4 H 8 + (but no PtC 3 H 6 + ) were observed and shown to have Pt + (ethene) and Pt + (ethene) 2 structures.…”
Section: Are There Other Adiabaticities/diabaticities Besides Spin?mentioning
confidence: 56%
“…This conclusion was confirmed by later repeating the experiment using a different apparatus operating under low-pressure conditions. 112 ) suggests that this species reacts rapidly with a fourth methane molecule under our experimental conditions.…”
Section: ■ Are There Other Adiabaticities/diabaticities Besides Spin?mentioning
confidence: 71%
“…Previously, we found that relatively standard density functional theory (DFT) methods proved sufficient to accurately predict the IR fingerprints, both in terms of frequencies and IR intensities, necessary for assigning the experimental IR spectra of [M,C,2H] + species with M 5d elements. 8–11,31 For the 4d elements M = Ru and Rh, the same conclusion holds, even though the assignment for the [Rh,C,2H] + species was complicated by the multi-reference character of RhCH 2 + . 20 In contrast, here, we find that these comparisons are not so straightforward for 3d elements.…”
Section: Introductionmentioning
confidence: 70%
“…This thermalization was recently illustrated by comparing the product formation upon activation of two methane molecules by Pt + , which in an ion trap leads to formation of ethene Pt + C 2 H 4 , whereas in a similar source to the one used here, the dehydrogenation was throttled, and a dimethyl product Pt + (CH 3 ) 2 is formed instead. 27,28 The reaction gas cell was cooled to a temperature of ∼200 K by liquid N 2 to facilitate the attachment of Ar atoms to the clusters, forming Ir n NO + -Ar p (p = 1−3). Internal energies of the clusters in good thermal equilibrium with the coolant gas were calculated to be 0.1−0.2 eV, or just below the binding energies of the Ar atom to the cluster (0.1−0.3 eV).…”
Section: Experimental Section the Adsorption Forms Of No On Ir Nmentioning
confidence: 99%